Organizational Justice and Organizational Citizenship Behavior: The Mediating Effect of Work Satisfaction - Widjajani, Susi; Rahmawati, Fitri; Yulianti, Eka (Universitas Muhammadiyah Magelang, 2021)
The use of village funds in 2020 is prioritized to finance the implementation of programs and activities in the field of development and empowerment of village communities. In order for the use of village funds to be managed optimally, organizational citizenship behavior (OCB) from the Village Apparatus is needed as the implementer. OCB behavior willemerge if Village Apparatus feel the existence of organizational justice and are satisfied with their work. This study aims to examine the mediating role of job satisfaction on the effect of organizational justice on OCB. The study population was 94 village apparatus in the Village Government of Padureso District, Kebumen Regency. The sampling technique used census techniques and data analysis using Path Analysis. The questionnaire used was adopted from previous research and its validity and reliability were tested. The results showed that there was an indirect influence between organizational justice on OCB, with job satisfaction as the mediating variable. The implication of this research is that there is a positive relationship between employees (village apparatus) and the organization if employees feel justice in the organization and job satisfaction